Knowledge and Attitude of Nursing Staff Regarding Preventability of Pressure Ulcers - Khadim, Aisha; Akbar, Iqra; Hashmat, Jamila; Sher, Nuzhat (Biological and Clinical Sciences Research Journal, 2025)
Pressure ulcers are a significant health concern in hospitalized patients and a key indicator of nursing care quality. Adequate knowledge and positive attitudes among nurses are essential for effectively preventing and managing pressure ulcers. Objective: To assess the level of knowledge and attitudes of nurses working at Medicare Hospital, Multan, regarding pressure ulcers. Methods: An exploratory cross-sectional study was conducted at Medicare Hospital, Multan, from February 2024 to February 2025. A total of 100 nurses from various departments were recruited based on availability. Knowledge was assessed using the 26-item Pressure Ulcer Knowledge Assessment Tool, which covered six key dimensions of pressure ulcer prevention and management. Attitudes were evaluated using a 13-item Attitudes Towards Pressure Ulcers Prevention (APuP) tool. Data were analyzed using SPSS version 25. Results: The overall mean knowledge score was 50.4% (12.01 ± 3.91), with only 10% of nurses achieving a high knowledge level (≥60%). The highest knowledge scores were recorded in the nutrition domain (80%), while the lowest were in risk assessment (40%). The mean attitude score was 68.2% (35.45 ± 12.00), below the satisfactory threshold of 75%. Only 55% of participants demonstrated a satisfactory attitude toward pressure ulcer prevention. Conclusion: Nurses at Medicare Hospital exhibited unsatisfactory levels of knowledge and suboptimal attitudes regarding pressure ulcer prevention. These findings highlight the urgent need for structured educational interventions and training programs to improve patient care outcomes related to pressure ulcers.